Assessment of sexual and reproductive health behaviour of school adolescents: A case study of Makwanpur, district, Nepal. - Adhikari, Ram Prasad (2018)
ABSTRACT: Adolescence is the period from 10-19 years, in which growth and development of physical, mental , social and emotional aspects heighten. The sexual desire arises among them with the growth and development processes. There is a high possibility of risky sexual behavior, which may lead them to the vulnerability of STIs early pregnancy and childbirth, mental tension and unsafe abortion. Such behaviours affect on sexual and reproductive health of adolescents. Sexual and reproductive health is associated with the whole life span of an individual, which is concerned with every activity regarding sexual and reproductive health behaviour. Early pregnancy and childbirth, involvement in unsafe sexual activities, unsafe abortion, prevalence of sexually transmitted infections, and lack of proper sexual and reproductive health services have an effect on the status of sexual and reproductive health of the adolescents. The main purpose of this research is to assess the sexual and reproductive health behaviour of school adolescents. This research is based on the philosophy ' pragmatism' pragmatism focuses on learning by doing, learning by trial and error and learning by experience. This research is bases on both the descriptive and the analytical research designs. This study has applied both qualitative and quantitative approach to interlink the result and information. The study area is Makwanpur. one of the districts of Nepal. It is a multi-cultural, multi-ethnic and multi-geographic district. It represents the whole Nepal because of its special characteristics. The required number of respondents for this study is 384, but respondents were taken as samples because of the probability of non-response. For the selection of required number of respondents , 5 boys and 5 girls from each grade (9 to 12) were selected in every school with the help of a systematic random sampling technique. The total number of sample respondents was 40 in every school. So, the number of schools required was 10. For that purpose, the district was divided into five strata with the help of proportionate stratified random sampling method. First of all, the district was divided into four strata on the basis of electoral regions. Then after the electoral region number 3 was also divided into two strata, where Hetauda Municipality became a new stratum because of its unique characteristics. Altogether, Makwnapur district was divided into five strata. The number of schools was selected in every stratum by using the formula of proportion (Px=Nx/N). The result shows that there is no significant difference (p=0.005 and p=0.011<0.05 in two-side)between the caste and sex of the respondents respectively and the prevalence of STIs. Similarly, there is no significant difference (p=0.000, p= 0.011 and p=0.004< 0.05 in two-side) between the sex, religion and caste of respondents respectively and premarital sex practice. Likewise, there is no significant difference (p=0.022, p=0.037 and p=0.000<0.05 in two-side) between the caste, religion and sex of respondents respectively and the use of contraception. In addition, there is no significant difference (p=0.000 and p=0.000<0.05 in two-side ) between the sex and location of the respondents respectively and the use of condom. Again, there is no significant difference (p=0.007<0.05) between the religion of the respondents and prevalence of STIs. The statistical analysis of the test power of hypothesis (1-Berror.Prob0 no. 1 (HO an H1) found that there is 97.91% chance of correctly rejecting the H0 and accepting the H1 and the statistical analysis of the test of power of hypothesis(1-Berror. Prob) no.2 found that there is 98.97% chance of correctly rejecting the H0 and accepting h1 with 400respondents. On the other hand, that the statistical analysis of the test of power of hypothesis (1-B err. prob) no.3 found that there is only 15.75% chance of correctly rejecting the H0 and accepting H1 with 400 respondents. So, the null hypothesis is accepted and alternative hypothesis is rejected with the less power of test of the hypothesis. The knowledge as well as the attitude of every aspect of the respondents on sexual and reproductive health seemed very good. But the practice or behaviour of the different aspect of sexual and reproductive health seemed mostly negative. It means that the overall sexual and reproductive health behaviour of the respondents seemed less. The behaviour on contraceptive use was found less than expected because there was not an easy access of contraception for the adolescents; they had to face various criticisms and mental torture if they try to get it. On the other hand, their age is low for the participation in sexual intercourse as well as they did not have enough and free time. Similarly, some of the respondents have got infected with STIs due to their carelessness during the period of sexual intercourse. Some of the respondents have the habit of masturbation to satisfy their sexual desire as well as to prevent from various STIs. Menstruation management is another main problem for adolescent girls at school during the period. All of the girls cannot buy the safety pad due to the poor economic conditions. So, They are using the pieces of old clothes, which lead them to the STIs as well as HPV. Likewise, early marriage is another problem in developing and undeveloped country like Nepal. The utilization of sexual and reproductive health services for adolescents is a great problem. The adolescents shy much to tell their problems as well as to show their reproductive organs in case of sexually transmitted infection. There is no separate ward or department for adolescents, where they might feel better to express their problems and take the services. It is necessary to include the adolescents in the target group for the easy access of contraceptives. The related Ministry should provide teacher training regarding sexual and reproductive health to develop the confidence to teach about it. Similarly, the school should manage and provide the menstrual pad for the adolescent girls during menstrual period at school. on the other hand, it is necessary to establish or manage the separate department or ward for the adolescents in every hospital in Nepal for the easy access and proper utilization of youth (adolescent) friendly reproductive health services. The curriculum Development Centre should modify or change the curriculum according to the change in contestual situations. Likewise, the parents should teach to their children about sexual and reproductive health related matters in time. The NGOs and INGOs should manage and conduct awareness programme on it. It is quite essential to study and research with the prominence on other prospective or all the areas of sexual and reproductive health covering the whole district as well as whole Nepal.